Cartilaginous Organoids: Advances, Applications, and Perspectives. Issue 1 (8th December 2022) - Yu, Yuhao; Wang, Juan; Li, Yamin; Chen, Yunsu; Cui, Wenguo
Abstract : Cartilage is a nonvascular and non‐neural, mesoderm‐derived tissue. Cartilage repair, especially articular cartilage repair and reconstruction, has always been a difficult problem in bone tissue engineering. The unique biological characteristics and mechanical structure of articular cartilage make articular cartilage reconstruction a great challenge. Currently, it is extremely difficult to construct artificial cartilage tissue with all the information of natural cartilage in vitro, which greatly restricts the development of cartilage tissue engineering. Organoid technology is a booming research topic in recent years, which can mimic the complex biological characteristics of organs or tissues in vivo by constructing them in vitro through tissue engineering techniques. Cartilage tissues constructed using organoid technology may provide us with a novel tool to study cartilage development, cartilage pathological processes, and cartilage repair. This review introduces the concept and research progress of cartilage organoids and focuses on the composition and cultivation methods of cartilage organoids and application scenarios, besides giving an outlook on the limitations of present research. Abstract : Cartilage tissue constructed using organoid technology may provide a novel tool for researchers to study cartilage development, pathological processes of cartilage, and cartilage repair. This review introduces the concept and research progress of cartilage organoids, focusing on the composition and culture methods of cartilage organoids and application scenarios, in addition to an outlook on prospective developments.